Soil Moisture Dynamics in Silvopastoral Systems In the Thar Desert of India - Sharma, S K; Rajora, M P; Mathur, B K (Annals of Arid Zone, 2016)
Variation in soil moisture level studied under different silvopastoral systems that were established in the arid alluvial soil at the Central Research Farm of the Central Arid Zone Research Institute, Jodhpur. Season and soil depth had significant control on soil moisture differences in all the systems. Minimum soil moisture (1.92%) was observed in the upper soil profile of grass strips in the silvopastoral system in summer. High soil moisture was recorded near tree bole or fallow soil strips between top feed tree rows in the afforested area. Rapid moisture depletion was observed during winter and summer in 0 to 60 em soil profile. Soil moisture status was higher in Prosopis cineraria - Cenchrus ciliaris than Hardwickia binata - C. ciliaris system under the similar soil and environmental conditions. Soil moisture status within 100 em soil profile of the plots having different densities of P. cineraria remained unaffected across the seasons.